Understanding adaptability a prerequisite for effective performance within complex environments - Burke, C. Shawn; Pierce, Linda G.; Salas, Eduardo (Advances in human performance and cognitive engineering research ;, 2006)
Adaptability is becoming a hallmark of effective performance at all levels and types of organizations. As complexity rises within the internal and external environments that organizations operate within it is no longer acceptable to be able to perform well when things go as expected; instead individuals, teams, and organizations must be able to continuously adapt their knowledge and skills in order to remain competitive in environments which are fluid, often ambiguous, and where multiple pathways to goal attainment exist. Thus, this volume takes a multi-disciplinary approach to increasing our understanding of adaptability within complex environments by integrating cutting-edge work done by experts in the field and compiling it in one volume. Specifically, the volume takes a systems approach in that chapters describe the manifestation and antecedents of adaptability at individual, team, and organizational levels. In addition, the volume presents work on the importance of cultural adaptability, visualization requirements, measurement approaches, training strategies, and selection for adaptive performance.